“Control De Gestión Del Área De Talento Humano Y El Comportamiento Organizacional En El Dispensario # 209 Del IESS, En El Cantón De Guayaquil”. - SALAS DAU, CECILIA (2015)
The Ecuadorian Institute of Social Security (IESS), is a highly recognized government entity, has about 8 million members, among which are public and private servers, the same as for access to their attention are governed by a defined schema. For the service arrives directly to its members, the IESS, serving in various units, such as Dispensary # 209, located in the city of Guayaquil, where specifically study the area of Human Resources. Throughout the history of health, there have been significant changes capable of meeting the immediate needs of external customers form, such as the Call Center, sophisticated service, often to make an appointment, the operator will ensures that there is no space or availability of turns. What creates conflict within the workspace. To improve service to users of health, is to suggest that a new method is determined to provide consultations to patients, giving low service call center. Furthermore, a mechanism that facilitates the development of technical-scientific and administrative, in order to improve the quality of care processes. These changes will not only be beneficial for members, but also for employees, because they see their satisfied customers are being encouraged to constantly improve.